Ubiquitous Working: Do Work Versus Non-work Environments Affect Decision-Making and Concentration? - Burmeister, Carolin P.; Moskaliuk, Johannes; Cress, Ulrike (Frontiers in Psychology, 2018)
New communication technologies and mobile devices have enabled knowledge workers to work independently of location and in more than one fixed environment (ubiquitous working). Previous research shows that physical environments can influence cognition and work performance. We manipulated environment (i.e., a virtual office as a typical work environment compared to a virtual garden as a non-work environment) and time pressure (i.e., inducing time pressure vs. no time pressure) in order to investigate whether the environment influences decision making and concentration. N = 109 students participated in this laboratory experiment. We posited a) that a work environment would activate a work-related schema which in turn would enhance concentration performance and make decisions more risky compared to non-work environments and b) that the environmental effect is more pronounced if time pressure is present compared to conditions where no time pressure is present. We found modest hypothesis-confirming main effects of environment on decision making and concentration but no interaction effect with time pressure. As we used an innovative methodology that entails several limitations, future research is needed to give insights into the process and to investigate whether results hold true for all types of work settings, work demands, or work activities.